Glass frit hermetic encapsulation for harsh environment multi-chip module application - Lim, Jun Zhang (2014)
This research project aims to investigate the suitability of glass frit bonding for multi-chip module (MCM) package encapsulation that needs to operate at a high temperature of 300°C and high pressure of 207 MPa. Since glass has the potential to bond well to alumina due to the chemical compatibility between the two materials, the use of glass frit for alumina to alumina bonding is considered a simple yet robust method that is often used for hermetic sealing of microelectronic packages. The materials used in the study were alumina substrate and bismuth-based glass frit paste 4115DS-1Ha from Asahi Glass Company (AGC). The study includes an initial characterisation of the glass frit, evaluation of the shear strength of the bonding, hermeticity test of the glass frit bonded MCM package and simulation on the high pressure testing on the package with glass frit. The average shear strength (shear test performed at 250°C) for samples after thermal aging at 300°C for 500 hours was 28.72 MPa. This value is approximately 3.6 times above the minimally required shear strength of 7.9 MPa according to the MIL-STD-883G specification. The hermeticity data of the sealed package after thermal aging at 300°C for 500 hours showed that the helium leak rate remained below the MIL-STD-883G specification of 5 × 10-8 atm cm3/s. This proves that glass frit bonding for MCM hermetic encapsulation for high temperature application is feasible. ANSYSTM simulation was carried out and results showed that cracks would not form on the glass frit layer upon pressurising the package at 207 MPa since the maximum principle stress is below the flexural strength of the AGC glass frit.